2014
DOI: 10.1007/s00280-014-2651-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine targets EGFRp-Tyr845 and inhibits EGFR-related signaling pathways to suppress the proliferation and invasion of gastric cancer cells

Abstract: Oxymatrine effectively suppressed the phosphorylation of EGFR (Tyr845), and EGFR was the target of oxymatrine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 27 publications
3
40
0
Order By: Relevance
“…Consistent with several previous studies that have reported the antitumor effects of matrine on cancer cells (18)(19)(20), the present study reinforced the findings of the anti-proliferative effects of oxymatrine in bladder cancer cells. The MTT assay indicated that oxymatrine decreased the cell survival rate in a dose-and time-dependent manner, which indicates Apoptotic ratio could not be analyzed for 2.50 mg/ml oxymatrine as necrosis occurred in a high number of cells and was therefore difficult to clearly determine.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with several previous studies that have reported the antitumor effects of matrine on cancer cells (18)(19)(20), the present study reinforced the findings of the anti-proliferative effects of oxymatrine in bladder cancer cells. The MTT assay indicated that oxymatrine decreased the cell survival rate in a dose-and time-dependent manner, which indicates Apoptotic ratio could not be analyzed for 2.50 mg/ml oxymatrine as necrosis occurred in a high number of cells and was therefore difficult to clearly determine.…”
Section: Discussionsupporting
confidence: 93%
“…metastasis and tumor-induced angiogenesis [17][18][19], which makes it an attractive target in cancer therapy. It has been reported that oxymatrine could suppress the proliferation and invasion of gastric cancer cells through EGFR-related signaling pathway [27]. We found that the phosphorylation level of EGFR was dramatically decreased with the increasing concentrations of WM130, suggesting that the effect of WM130 on HCC cells may be through the suppression of EGFR phosphorylation and EGFR-mediated signaling pathway.…”
Section: Wm130 Inhibited the Growth Of Hcc Xenograft Tumors In Nude Micementioning
confidence: 84%
“…OMT has been extensively investigated for antitumor effects against various cancers [15], including lung [12], gastric [13], pancreatic [11], and breast [14]. However, to the best of our knowledge, the antitumor effects of OMT on GBM have yet to be fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro and in vivo studies have shown that OMT inhibits cell proliferation and induces apoptosis in various types of cancers [1115]. OMT has also been shown to decrease the migratory ability of different cancer cell lines [13, 15]. In this study, we investigate the anticancer properties of OMT on human glioma cells and evaluate their underlying mechanisms.…”
Section: Introductionmentioning
confidence: 98%